Biaya Tambahan Yang Dibayar Pasien Rawat Jalan Akibat Penulisan Resep Tidak Sesuai Dengan Formularium Rumah Sakit - Supardi, Sudibyo; Azis, Sriana; Herman, MJ.; Jamal, Sarjaini; Mun'im, Abdul; Raharni, Raharni (Majalah Ilmu Kefarmasian, 2005)
Almost all district public hospital already has their own formulary. The aims of study are to obtain percentage of noncompliance with the public hospital formulary, to obtain the average additional cost be paid by outpatients as a result of noncompliance with the hospital formulary, and to obtain the average of the outpatient's ability to pay for treatment. A cross sectional study has been carried out to 120 patients in RSU Kabupaten K and 100 patients in RSU Kabupaten B. Subjects of the study were adult outpatients with TB, hypertension and diabetes. Data were collected by well-trained district public hospital staff in interviewing patients. The questioner was first tried out to patients at RSU Kota Jakarta Timur. Data were analyzed by cost analysis. Results of the study are difference in drug item with formulary in RSU Kabupaten K is 66,7% for TB, 96,6% for hypertension; where as in RSU Kabupaten B 44,8% for TB, 82,3% for hypertension and 76,7% for diabetes. Average additional cost that must be paid by outpatients per encounter in RSU Kabupaten K is Rp 10.060 for TB, Rp 26.552 for hypertension; while in RSU Kabupaten B is Rp 5.818 for TB, Rp 8.956 for hypertension and Rp 15.218 for diabetes. The average outpatient's ability to pay for treatment in RSU Kabupaten K is Rp 19.807 and in RSU Kabupaten B is Rp 15.301, which are both less than outpatient treatment cost per encounter.